Salvage endoscopic resection in patients with esophageal adenocarcinoma after chemoradiotherapy - Noordzij, Irma C.; Curvers, Wouter L.; Huysentruyt, Clément J.; Nieuwenhuijzen, Grard A.P.; Creemers, Geert-Jan; van der Sangen, Maurice J.C.; Schoon, Erik J. (Endoscopy International Open, 2018)
Background and study aims For early esophageal adenocarcinoma, endoscopic resection is an accepted curative treatment with an excellent long-term prognosis. Case series from Japan have reported endoscopic resection of residual esophageal squamous cell carcinoma after chemoradiotherapy. This is the first report describing endoscopic resection of residual esophageal adenocarcinoma after chemoradiotherapy. Two patients with advanced esophageal adenocarcinoma had been treated with chemoradiotherapy because comorbidity precluded esophageal resection. When residual tumor was observed endoscopically, complete remission was achieved by salvage endoscopic therapy alone or in combination with argon plasma coagulation (APC). Both patients achieved long-term sustained remission and died of non-tumor-related causes.